A new ectoparasitic distichodontid of the genus Eugnathichthys (Characiformes: Citharinoidei) from the Congo basin of central Africa, with a molecular phylogeny for the genus - Stiassny, Melanie L.j.; Denton, John S.s.; Iyaba, Raoul J.c. Monsembula (Zootaxa, 2013)
A new species of ectoparasitic distichodontid, Eugnathichthys virgatus, is described from localities in the central and western Congo basin. The new species is a fin-eater even at small sizes and, in common with congeners, is capable of biting off sections of heavily ossified fin-rays of large prey species. Prior to the present study, two species were included in this distinctive distichodontid genus: the type species, Eugnathichthys eetveldii, and a second species, E. macroterolepis, both of which are widely distributed throughout much of the Congo basin. Morphologically, E. virgatus is readily distinguished from its two congeners based on a combination of meristic and morphometric attributes. The new species possesses a unique pigmentation pattern, a reduced number of pectoral-fin rays, and a markedly reduced dentition on the fifth ceratobranchial elements of the pharynx, all of which are derived features considered diagnostic for the new species. With molecular data the species is further diagnosed by four apomorphic, non-synonomous nucleotide transitions in two sampled genes (NADH dehydrogenase subunit 2 and glycosyltransferase). Phylogenetic analysis of those mtDNA and ncDNA markers supports a sister-group relationship between E. virgatus and E. eetveldii rather than with E. macroterolepis, the species with which it bears closest phenetic similarity.